Pengungkapan Pengendalian Internal : Esensi Komisaris Independen dan Struktur Kepemilikan Industri Perbankan di Indonesia - Agus Ismaya Hasanudin; Dadan Ramdhani; Andry Dwi Fajar (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to examine the influence of independent commissioners on the disclosure of internal controls with ownership structure as a moderating variable.This study uses the sempel of the banking industry sector in Indonesia during 2013-2018. The sampling method used in this study is purposive sampling, the number of companies that made sempel this company is 119 companies with observations for 3 years. Data processing used by researchers is multiple regression analysis.The results of this study show that independent commissioners negatively affect the disclosure of internal controls, while the government ownership structure strengthens the influence of independent commissioners on disclosure of internal controls and private ownership structure weakens the influence of independent commissioners on the disclosure of internal controls